Real-World Effectiveness of Mineralocorticoid Receptor Antagonists in Primary Aldosteronism - Yuta Tezuka; Yuta Tezuka; Adina F. Turcu (Frontiers in Endocrinology, 2021)
ObjectiveTo investigate how often target renin is pursued and achieved in patients with primary aldosteronism (PA) and other low renin hypertension (LRH) treated with mineralocorticoid receptor antagonists (MRAs), as reversal of renin suppression was shown to circumvent the enhanced cardiovascular and renal morbidity and mortality in these patients.Patients and MethodsWe conducted a retrospective cohort study of patients with PA and LRH treated with MRAs in an academic outpatient practice from January 1, 2000, through May 31, 2020.ResultsOf 30,777 patients with hypertension treated with MRAs, only 7.3% were evaluated for PA. 163 patients (123 with PA) had renin followed after MRA initiation. After a median follow-up of 124 [interquartile range, 65-335] days, 70 patients (43%) no longer had renin suppression at the last visit. The proportion of those who achieved target renin was higher in LRH than in PA (53% vs. 40%). Lower baseline serum potassium, lower MRA doses, and beta-blocker use were independently associated with lower odds of achieving target renin in PA, while male sex was associated with target renin in LRH. Overall, 50 patients (30.7%) had 55 adverse events, all from spironolactone, and 26 patients (52%) were switched to eplerenone or had a spironolactone dose reduction.ConclusionDespite evidence that reversal of renin suppression confers cardio-renal protection in patients with PA and LRH, renin targets are followed in very few and are achieved in under half of such patients seen in an academic setting, with possibly even lower rates in community practices.